Information, management and participation : a new approach from public health in Brazil - Notarbartolo di Villarosa, Francesco, 1960- (Frank Cass, 1998)
In order to alleviate poverty, people-oriented projects (those dealing with activities such as institutional development, health, family planning, education, and rural development) must be well-targeted towards the most vulnerable groups. However, official 'top-down' information is incapable of identifying, prioritising and 'marking out' these groups at a local level, and the result is too often an unfair, inefficient and ineffective allocation and use of the resources of social programmes. The author argues that a 'process approach' is often necessary to geneate relevant knowledge about local.